A Value-Based Approach to Qur'anic Exegesis: A Study of Qur'anic Address in Surah Luqman - K. M. A. Ahamed Zubair (Ahad: Multidisciplinary Journal of Islamic Studies, 2026)
This research aims to apply the value-based approach in Qur'anic exegesis through an applied model on the verse of the Qur'anic address to humanity in Surah Luqman. It seeks to highlight an exegetical approach that has not been systematically explored as an independent field, despite its implicit presence in many classical commentaries. The research adopts a deductive method to extract values from the Qur'anic address in Surah Luqman (31:33); a descriptive method to describe and classify the values; and an analytical method to analyze and link them to contemporary realities. The research concludes by defining the value-based approach in exegesis as the exegete's inclination to clarify Qur'anic verses from the perspective of the Islamic values they contain, explicitly or implicitly. This approach aids in embodying the Qur'an and applying it in reality. Furthermore, the verse of the Qur'anic address to humanity in Surah Luqman encompasses thirteen values: five negative and eight positive values identified within the single verse. And studying the value-based approach in interpreting the Qur'anic address to humanity in Surah Luqman reveals its importance in contributing to value-based education and modifying human behavior. This opens the horizon for further research into all Qur'anic verses to uncover their value-based dimension.